Developing and Testing a Personalized, Evidence-Based, Shared Decision-Making Tool for Stent Selection in Percutaneous Coronary Intervention Using a Pre-Post Study Design. Issue 2 (February 2019) - Chhatriwalla, Adnan K.; Decker, Carole; Gialde, Elizabeth; Catley, Delwyn; Goggin, Kathy; Jaschke, Katie; Jones, Philip; deBronkart, Dave; Sun, Tony; Spertus, John A.
Abstract : Background: Drug-eluting stents reduce the risk of restenosis in patients undergoing percutaneous coronary intervention, but their use necessitates prolonged dual antiplatelet therapy, which increases costs and bleeding risk, and which may delay elective surgeries. While >80% of patients in the United States receive drug-eluting stents, less than a third report that their physicians discussed options with them. Methods and Results: An individualized shared decision-making (SDM) tool for stent selection was designed and implemented at 2 US hospitals. In the postimplementation phase, all patients received the SDM tool before their procedure, with or without decision coaching from a trained nurse. All patients were interviewed with respect to their knowledge of stents, their participation in SDM, and their stent preference. Between May 2014 and December 2016, 332 patients not receiving the SDM tool, 113 receiving the SDM tool with coaching, and 136 receiving the tool without coaching were interviewed. Patients receiving the SDM tool + coaching, as compared with usual care, demonstrated higher knowledge scores (mean difference +1.8; P <0.001), reported more frequent participation in SDM (odds ratio=2.96; P <0.001), and were more likely to state a stent preference (odds ratio=2.00; P <0.001). No significant differences were observed between the use of the SDM tool without coaching and usual care. For patients who voiced a stent preference, concordance between stent desired and stent received was 98% for patients who preferred a drug-eluting stent and 50% for patients who preferred a bare metal stent. The SDM tool (with or without coaching) had no impact on stent selection or concordance. Conclusions: An SDM tool for stent selection was associated with improvements in patient knowledge and SDM only when accompanied by decision coaching. However, the SDM tool (with or without coaching) had no impact on stent selection or concordance between patients' stent preference and stent received, suggesting that physician-level barriers to SDM may exist. Clinical Trial Information: URL:https://www.clinicaltrials.gov . Unique Identifier: NCT02046902. Abstract : Supplemental Digital Content is available in the text.